The Art of Devising and Revising - A Study on the Products and Target Group Strategies of Telgu TV Channels - Ramana Murthy, K. V.; Achalapathi, K. V. (Indian Journal of Marketing, 2010)
The success of a channel depends on the quality of products offered to meet desired levels of satisfaction of the target groups. The product and target group strategies are evolved on the basis of SWOT analysis, resources available with the channel, products developed by the competitors and ratings of the programmes. The outcomes are dependent on devising the programmes by the TV channels and their revision at regular intervals. As per Christopher Lovelock and Jochen Wirtz, "All service organisations face choices about the types of products to offer and the operational procedures to use in creating them. In a customer focused organisation, these choices are often driven by market factors, with firms seeking to respond to the expressed needs of specific market segments and to differentiate the characteristics of their offerings against those of competitors. A more radical form of product innovation involves exploiting technological developments to satisfy latent needs that customers have not previously articulated or even recognized."